(untitled) (Al-Academy, 2021)
eroticism formed a basic focus in contemporary studies and caused a problematic clash in terms of terminology, as some interpreted it by pornography and another interpreted it as aesthetic, so this research came to seek to decipher this terminological clash, and to be known as erotech in terms of cognitive significance, Accordingly, the research culminated in four chapters. The first chapter (Methodological Framework) talks about the research problem that came according to the following question: “How is the erotic act built in the theatrical text and what are the epistemic connotations that express its subjectivity? Then followed by the importance of research and the need for it, then the objective of the research, and the boundaries of research that were determined in time (2009) and spatially / Iraq, and objectively / about me by studying the erotica as a sign The chapter was concluded by defining the terms and defining them As for the second chapter, it consists of two researches, the first one is called: “Aerotec is an epistemic connotation” and the second is “Aerotec and its manifestations in the theatrical text.” Then the chapter was concluded with the results of the theoretical framework. ) Included On the research community, which consisted of three plays, then the research sample that was formed from a play taken from the research community by the intentional method and adopted the results of the theoretical framework as a tool for research to conclude the chapter by analyzing the research sample, then the fourth chapter came under the name of results and conclusions and the most important of these The results (the text formed an aesthetic and pictorial space, through body, the female body (Dzdemonh), and overwhelmed by the details of (Bailoger), to broadcast through his vocabulary erotica erotic sexual instinct on the tongue (Iago), and conclusions and it was the most important (try the text that gives the receiver a form aesthetically pleasing geography The female body) to conclude the research with a list of references and sources .